2013
DOI: 10.1016/j.cellsig.2012.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis regulation by salubrinal through eIF2α mediated differentiation of osteoclast and osteoblast

Abstract: Nuclear factor-κB (NF-κB) ligand (RANKL) was shown to induce osteoclast differentiation by increasing the expression of c-Fos, NFATc1 and TRAP. Salubrinal treatment to bone marrow macrophage (BMM) cells, however, significantly blocked NFATc1 expression and osteoclast differentiation by RANKL. Overexpression of NFATc1 further confirmed that NFATc1 is a key factor affected by salubrinal in osteoclast differentiation by RANKL. Unexpectedly, NFATc1 and c-Fos mRNA expressions were not affected by salubrinal, implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
57
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 30 publications
5
57
0
Order By: Relevance
“…ER stress-induced apoptosis acts as a causative agent of osteoporosis. [22][23][24][25][26] Our observations indicated that 17b-E 2 may contribute to protective effects on ER stress-induced apoptosis in osteoblasts. Osteoporosis is a highly prevalent disease and results in massive costs both to the individual and to the society through associated fragility fractures.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…ER stress-induced apoptosis acts as a causative agent of osteoporosis. [22][23][24][25][26] Our observations indicated that 17b-E 2 may contribute to protective effects on ER stress-induced apoptosis in osteoblasts. Osteoporosis is a highly prevalent disease and results in massive costs both to the individual and to the society through associated fragility fractures.…”
Section: Discussionmentioning
confidence: 58%
“…[17][18][19][20][21] ER stressinduced apoptosis of osteoblasts has also been implicated in the pathogenesis of osteoporosis. [22][23][24][25][26] Our study found that the MC3T3-E1 cells, the mouse calvaria osteoblasts, were led into the decrease of cellular viability in response to ER stress. However, pretreatment with 17b-E 2 can increase the viability of osteoblasts in ER stress in a dose-dependent manner between 0.1 nM and 100 nM and the effects plateaued at 10 nM.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations